2020
DOI: 10.1002/joc.6933
|View full text |Cite
|
Sign up to set email alerts
|

Tropospheric thermal field variability over Poland in the context of climate change

Abstract: Based on the results of radiosounding measurements from all Polish aerological stations, an analysis of temperature changes in the troposphere and tropopause over Poland was carried out. The study was performed for data from 1981 to 2018 at 00 UTC for five main isobaric surfaces (MISs): 850, 700, 500, 300 and 200 hPa and for the tropopause. It was found that the tropospheric temperature variability is highest in the cold months of the year and lowest in summer. Annual temperature variability in the upper tropo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 49 publications
(69 reference statements)
0
1
0
Order By: Relevance
“…The observed increase in air temperature in the lower and middle troposphere over Poland (Urban et al, 2021) confirmed by measurements from ground stations in the Western Sudetes (Migała et al, 2016) with a simultaneous increase in sunshine duration (Urban, Migała, & Pawliczek, 2018) and changes in the frequency of circulation types with warm marine air masses affect various indicators of SC and its occurrence. An analysis of the mean dates of the start and end of SC in the Western Sudetes shows that it appears earliest in the highest parts of the mountains (early October) and progresses down the slopes (mid‐November) and disappears earliest in the lower parts of the slopes (early April) and progresses up the slopes and toward the tops of the mountains (late May).…”
Section: Resultsmentioning
confidence: 61%
“…The observed increase in air temperature in the lower and middle troposphere over Poland (Urban et al, 2021) confirmed by measurements from ground stations in the Western Sudetes (Migała et al, 2016) with a simultaneous increase in sunshine duration (Urban, Migała, & Pawliczek, 2018) and changes in the frequency of circulation types with warm marine air masses affect various indicators of SC and its occurrence. An analysis of the mean dates of the start and end of SC in the Western Sudetes shows that it appears earliest in the highest parts of the mountains (early October) and progresses down the slopes (mid‐November) and disappears earliest in the lower parts of the slopes (early April) and progresses up the slopes and toward the tops of the mountains (late May).…”
Section: Resultsmentioning
confidence: 61%